(untitled) (Advancements in Homeopathic Research, 2026)
Introduction: Functional digestive disorders such as dyspepsia, bloating, and acidity are common and often recurrent, affecting quality of life and increasing healthcare burden. Given the need for well-tolerated therapeutic options, this study aimed to evaluate the real-world effectiveness, speed of action, safety, and physician recommendation of Dizester® Homeopathic Digestive Tonic in managing functional digestive complaints. Materials and Methods: A structured Google Form survey was designed to collect feedback from prescribing physicians across different regions. The questionnaire assessed speed of action, clinical effectiveness (5-point rating scale), adverse effects, and recommendation patterns. Of 222 total respondents, data from 151 prescribing physicians were included for descriptive analysis. Results: The majority of physicians reported early symptomatic improvement, with 48.3% indicating immediate relief and 38.4% observing benefit within 15 days; overall, 94.7% noted improvement within 4 weeks. High effectiveness ratings were observed, as 92.7% assigned scores of 4 or 5, and 99.3% rated the product 3 or above. The formulation demonstrated a favorable tolerability profile, with 99% of respondents reporting no undesirable effects; isolated cases of mild gastric burning were reported but not clearly attributable to treatment. Additionally, 96.7% indicated willingness to recommend the product, and the majority of feedback (85%) was positive or highly positive. Conclusion: Real-world evidence and physician feedback suggest that Dizester® Digestive Tonic is effective, rapidly acting, and well-tolerated in routine clinical practice. The findings support its clinical utility in managing functional digestive complaints and highlight the need for further prospective controlled studies to strengthen the evidence base